Nb 활용 탄질소 스테인리스강의 부동태 및 대기산화 피막 보호성 연구 - 이창근; Chang-geun Lee; 하헌영; Heon-young Ha; 이태호; Tae-ho Lee; 조경목; Kyung-mox Cho (대한금속·재료학회지, 55(12), 2017)
The effects of Nb on grain refinement and the pitting corrosion resistance of Febalance18Cr10 Mn0.3C0.3NxNb (x = 0.1 and 0.2 wt%) high interstitial alloys were investigated through microstructure analysis and potentiodynamic polarization tests. The resistance to pitting corrosion of the two alloys, covered with a passive film and an air-formed oxide films, was also examined. As the Nb content increased from 0.1 to 0.2 wt%, the grain size decreased, the volume fraction of Nb(C,N) particles increased, and the pitting potential was elevated. In addition, the two alloys covered with the passive film exhibited higher pitting potentials than the alloys with the air-formed oxide films. The physico-chemical and electronic properties of the passive film formed in an aqueous environment, and air-formed oxide of the two alloys were examined using X-ray photoelectron spectroscopy and Mott-Schottky analysis. As a result, it was revealed that the defect density level in the passive film was the dominant factor in determining the pitting corrosion resistance of the specimens. Nb addition was found to promote the formation of a protective passive film with low defect density, which resulted in the increase in the pitting potential. Moreover, the fact that the point defect density of the passive film was smaller than the air-formed oxide films was observed in both alloys, which can explain the higher pitting corrosion resistance of the passivated specimen than the specimen covered with an air-formed oxide film. (Received July 5, 2017; Accepted September 25, 2017)